Partial Glossectomy and Reconstruction for Excision of a Tumor of the Tongue in a Dog - N.Krishnaveni; M. Madeena Begum; E. Kalaiselvan (The Indian Veterinary Journal, 2025)
A 13 year old female white Spitz was presented with a history of drooling of blood mixed saliva for the past 1 month. Oral cavity examination revealed small lemon sized soft mass on the dorsal aspect of the right side of the tongue. Clinical examination revealed normal vital parameters. Presumptive diagnosis was made as lingual tumor based on the gross appearance. Under general anaesthesia surgical excision of the tumor with wide margin of safety and tongue reconstruction was performed. Histopathology confirmed the tumor as amelonotic melanoma. Animal had an uneventful recovery with no recurrence.